Integrating smartwatch-based out-of-hospital cardiac arrest detection into resuscitation systems: a focus group study of community responder perspectives - Marijn Eversdijk; Babette J.W. van der Eerden; Dick L. Willems; Willem J. Kop; Mirela Habibović; Marieke A.R. Bak (Resuscitation Plus)
Background: Smartwatch-based solutions for out-of-hospital cardiac arrest (OHCA) detection are increasingly explored to enhance survival outcomes, especially in unwitnessed cases. However, the perspectives of community responders, who play a critical role in early responding to resuscitation alerts, are not yet known. Exploring their current experiences and perspectives on this new technology is important for successfully developing and integrating these innovations into existing resuscitation systems. Methods: Four semi-structured focus group discussions (FGDs) were conducted with 15 community responders in the Netherlands, recruited through the national cardiac arrest emergency network. Each FGD comprised two discussion topics: (1) integrating smartwatch-based OHCA detection into the current resuscitation system and (2) mitigating the burden of this technology on community responders. Verbatim transcripts were inductively coded for recurring themes. Results: The FGDs revealed 54 unique codes that were grouped into four themes: (1) Missing information about the cause of the alert; (2) decision-making regarding accepting the alert, (3) challenges in reaching the location and (4) availability of aftercare for community responders. Conclusion: This study identifies target topics that require attention in order to optimise community responders involvement in the implementation of smartwatch-based OHCA detection. Community responders indicated communication with the emergency dispatch centre, training with smartwatch-initiated scenarios and opt-in functionalities for responding to potential impactful situations as key factors to enhance the acceptability and feasibility. These factors ultimately aim to facilitate faster and more effective resuscitation following smartwatch-initiated alerts.